So sánh:
\(\left(0,49\right)^{36}và\left(0,512\right)^{24}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)
(0,49)36=[(0,49)3]12=(0,117649)12
(0,512)24=[(0,512)2]12=(0,262144)12
=>(0,49)36<(0,512)24
Bài 1:
\(A=26^2-24^2=\left(26-24\right)\left(26+24\right)=2\cdot50=100\)
\(B=27^2-25^2=\left(27-25\right)\left(27+25\right)=2\cdot52=104\)
=>A<B
Bài 2:
\(4\left(x+1\right)^2+\left(2x-1\right)^2-8\left(x-1\right)\left(x+1\right)=11\)
=>\(4\left(x^2+2x+1\right)+4x^2-4x+1-8\left(x^2-1\right)=11\)
=>\(4x^2+8x+4+4x^2-4x+1-8x^2+8=11\)
=>4x+13=11
=>4x=-2
=>\(x=-\dfrac{1}{2}\)
\(B=24\left(5^2+1\right)\left(5^4+1\right)\left(5^8+1\right)\left(5^{16}+1\right)\)
\(=\left(5^2-1\right)\left(5^2+1\right)\left(5^4+1\right)\left(5^8+1\right)\left(5^{16}+1\right)\)
\(=\left(5^4-1\right)\left(5^4+1\right)\left(5^8+1\right)\left(5^{16}+1\right)\)
\(=\left(5^8-1\right)\left(5^8+1\right)\left(5^{16}+1\right)\)
\(=\left(5^{16}-1\right)\left(5^{16}+1\right)\)
\(=5^{32}-1< 5^{32}\)
Vậy \(B< A\)
\(x=\left(1-\frac{1}{2}\right).\left(1-\frac{1}{4}\right)\left(1-\frac{1}{6}\right)\left(1-\frac{1}{8}\right)\left(1-\frac{1}{10}\right)\)
\(=\frac{1}{2}.\frac{3}{4}.\frac{5}{6}.\frac{7}{8}.\frac{9}{10}=\frac{63}{256}< \frac{63}{210}=0,3\)
\(x=\sqrt{0,1}>\sqrt{0,09}=0,3\)
=> y<x
\(\left( { - 1} \right) + \left( { - 3} \right) = - \left( {1 + 3} \right) = - 4\)
\(\left( { - 3} \right) + \left( { - 1} \right) = - \left( {3 + 1} \right) = - 4\)
\( \Rightarrow \left( { - 1} \right) + \left( { - 3} \right) = \left( { - 3} \right) + \left( { - 1} \right)\)
\(\left( { - 7} \right) + \left( { + 6} \right) = - \left( {7 - 6} \right) = - 1\)
\(\left( { + 6} \right) + \left( { - 7} \right) = - \left( {7 - 6} \right) = - 1\)
\( \Rightarrow \left( { - 7} \right) + \left( { + 6} \right) = \left( { + 6} \right) + \left( { - 7} \right)\)
\(\begin{array}{l}\left[ {\left( { - 3} \right) + 4} \right] + 2 = \left( {4 - 3} \right) + 2\\ = 1 + 2 = 3\end{array}\)
\(\begin{array}{l}\left( { - 3} \right) + \left( {4 + 2} \right) = \left( { - 3} \right) + 6\\ = 6 - 3 = 3\end{array}\)
\(\begin{array}{l}\left[ {\left( { - 3} \right) + 2} \right] + 4 = - \left( {3 - 2} \right) + 4\\ = - 1 + 4 = 3\end{array}\)
\(\left(0,49\right)^{36}=\left[\left(0,7\right)^2\right]^{36}=\left(0,7\right)^{72}\)
\(\left(0,512\right)^{24}=\left[\left(0,8\right)^3\right]^{24}=\left(0,8\right)^{72}\)
Vì 0,7<0,8 suy ra \(\left(0,7\right)^{72}< \left(0,8\right)^{72}\)
Vậy \(\left(0,49\right)^{36}< \left(0,512\right)^{24}\)
(0,49)36=[( 0,7)2]36=(0,7)72 (1)
(0,512)24=[(0,8)3]24=(0,8)72(20
Từ (1) và (2) vậy (0,49)36<(0,512)24